Legal Protection of the Rights of Workers/Laborers in Banturung Sub-District Bukit Batu Kota Palangka Raya Based on Law Number 13 of 2003 Concerning Manpower - Oktarianus Kurniawan; Ronaldi; Rizki Setyobowo Sangalang; Alvin Nur Aulia (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
During the covid-19 pandemic that occurred in Indonesia, which affected the economic sector, there were many layoffs by employers, except in Banturung Village, Bukit Batu District, Palangka Raya City. In Law Number 13 of 2003 concerning Manpower, it is explained about the rights and obligations of a worker in carrying out his work, in which the Act serves to protect and limit the status of the rights and obligations of workers from employers (entrepreneurs) in accordance with human dignity in the scope of work. In the conditions of the Covid-19 pandemic, both employers and workers are disadvantaged, because the weak economy makes people's purchasing power decrease and employers cannot rotate their business capital and take steps to unilaterally terminate employment relations. In Law Number 13 of 2003 concerning Employment, workers who experience termination of employment must be given severance pay.